The epidemiology of avian tuberculosis in White-winged Wood Ducks Cairina scutulata at The Wildfowl and Wetlands Trust, Slimbridge Centre (1976-91) - Cromie, Ruth L; Brown, Martin J; Stanford, J L (Wildfowl, 1965)
The disease avian tuberculosis is affecting drastically the management of White-winged Wood Ducks Cairina scutulata in captivity. An epidemiological survey of the disease in adult White-winged Wood Ducks at The Wildfowl and Wetlands Trust, Slimbridge Centre, (1976-91) has been carried out. The disease was recorded in 102 out of 121 (84%) post mortem (PM) examinations during the study period. The greatest proportion of deaths from the disease occurred in summer and winter rather than spring and autumn. Although there was no difference in the total numbers of males and females dying of the disease, the greatest number of female deaths occurred during the summer, probably due to the stress of breeding. The study highlights the importance of screening for avian tuberculosis in relation to potential reintroduction programmes. Recommendations to control the disease are put forward.